2007
DOI: 10.1007/s10549-007-9819-x
|View full text |Cite
|
Sign up to set email alerts
|

In situ levels of oestrogen producing enzymes and its prognostic significance in postmenopausal breast cancer patients

Abstract: Protein expression of stromal aromatase may serve as a significant prognostic marker in ER-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…In order to evaluate whether there was a relationship between nuclear and cytoplasmic FOXL2 expression, we performed a correlation test, and the results demonstrated no significant correlation (RR=1.07, 95% CI=0.94-1.22, P=0.31). In addition, the present patient cohort was previously immunohistochemically stained for aromatase (3) and cases with a tumour expressing nuclear FOXL2 were more likely to have a concomitant expression of aromatase in the stroma and/or in the cytoplasm of cancer epithelial cells (Or=2.54, 95% CI=1.06-6.09, P=0.034; Or=3.03, 95% CI=1.31-7.02, P=0.008, respectively) ( Table I). Using mCF7 cells, we performed Western blot analysis in order to examine the specificity of the antibody as well as the basal level of FOXL2.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to evaluate whether there was a relationship between nuclear and cytoplasmic FOXL2 expression, we performed a correlation test, and the results demonstrated no significant correlation (RR=1.07, 95% CI=0.94-1.22, P=0.31). In addition, the present patient cohort was previously immunohistochemically stained for aromatase (3) and cases with a tumour expressing nuclear FOXL2 were more likely to have a concomitant expression of aromatase in the stroma and/or in the cytoplasm of cancer epithelial cells (Or=2.54, 95% CI=1.06-6.09, P=0.034; Or=3.03, 95% CI=1.31-7.02, P=0.008, respectively) ( Table I). Using mCF7 cells, we performed Western blot analysis in order to examine the specificity of the antibody as well as the basal level of FOXL2.…”
Section: Resultsmentioning
confidence: 95%
“…There have been many studies on the prognostic significance of aromatase in breast cancer, although no conclusive results have been reached (1,2). We have previously found that aromatase is a significant prognostic factor in post-menopausal breast cancer patients, with an improved relapse-free survival in cases with stromal expression (3).…”
Section: Introductionmentioning
confidence: 96%
“…The increase in breast fat is also likely to have an adverse impact on the breast cancer pathogenesis. It has been known for at least two decades that breast stroma, in particular, breast fat, actively produces estrogens [4][5][6][7][19][20][21][22][23][24][25]. The following is an overview of some of these studies and reviews.…”
Section: The Impact Of Menopause and Hrt On Breast Cancer Riskmentioning
confidence: 99%
“…Over the last 2 decades, it has become abundantly clear that the normal and malignant breast has all the enzymes necessary to produce oestrogens locally, within the breast itself. This intracrine and paracrine process has been recently reviewed by several authors [36][37][38][39][40][41]. Breast tissue levels of oestrogens are much higher than serum, both before and after menopause [36][37][38][39][40][41].…”
Section: Local Breast Production Of Oestrogen Is Far More Important Tmentioning
confidence: 99%
“…Most breast malignancies are surrounded by tissues (fat, stroma and sometimes malignant epithelial cells) with enhanced aromatase activity -even compared with aromatase activity within other areas of the same breast [36,37,40]. Professor Pasqualini's group have shown that the sulphatase enzyme pathway which converts oestrone sulphate (the most abundant oestrogen in serum) into oestrone, is 100-500 times more active in human breast cancer tissue than aromatase [37].…”
Section: Local Breast Production Of Oestrogen Is Far More Important Tmentioning
confidence: 99%